2005
DOI: 10.1016/s1472-6483(10)60946-7
|View full text |Cite
|
Sign up to set email alerts
|

Management of poor ovarian responders in IVF

Abstract: Correct controlled ovarian stimulation is of paramount importance in assisted reproductive technologies. Therefore, analysis of the ovarian reserve of the patient is mandatory to tailor the best ovarian stimulation regimen. When the ovarian reserve is reduced, the induction of a multifollicular growth remains a challenge. Several factors could be associated with reduced ovarian response. However, reduced ovarian reserve either in older patients or in young patients represents the most frequent aetiological fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
0
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(78 citation statements)
references
References 129 publications
4
63
0
8
Order By: Relevance
“…Unfortunately, w9-24% of all IVF cycles undertaken fail to respond to standard ovarian stimulation regimens, due to poor ovarian response (POR) to hormonal stimulation (Abir et al 2008). Currently, the management of POR patients represents a significant therapeutic challenge (Hazout et al 2009, Yovich & Stanger 2010, such that various alternative forms of clinical intervention have either been ineffective or lack sufficient scientific evidence necessary to support clinical application (Ubaldi et al 2005). Recently, we have demonstrated that the administration of exogenous growth hormone (GH) supplementation, in conjunction with standard ovarian stimulation regimens, resulted in significantly higher embryo implantation and clinical pregnancy rates compared with those not treated with GH (Yovich & Stanger 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, w9-24% of all IVF cycles undertaken fail to respond to standard ovarian stimulation regimens, due to poor ovarian response (POR) to hormonal stimulation (Abir et al 2008). Currently, the management of POR patients represents a significant therapeutic challenge (Hazout et al 2009, Yovich & Stanger 2010, such that various alternative forms of clinical intervention have either been ineffective or lack sufficient scientific evidence necessary to support clinical application (Ubaldi et al 2005). Recently, we have demonstrated that the administration of exogenous growth hormone (GH) supplementation, in conjunction with standard ovarian stimulation regimens, resulted in significantly higher embryo implantation and clinical pregnancy rates compared with those not treated with GH (Yovich & Stanger 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Among the various causes of DOR, abnormal immune function may be a great contributor to this phenomenon (2). Patients with DOR often become infertile and have a poor response to in vitro fertilization (IVF) (3,4). Researchers have developed different protocols to solve this problem, but none of them has proven to be ideal for such patients (5-7).…”
Section: Introductionmentioning
confidence: 99%
“…The aim of controlled ovarian hyperstimulation is to reduce the cycle cancellation rate, increment the number of oocytes and top-quality embryos and ensure better results in terms of pregnancy rates [2][3][4][5]. However, in different clinical situations such as reduced ovarian reserve, previous oncologic or estrogen-dependent disease the natural cycle continue to be considered the method of choice for IVF treatment [6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%